The large-scale cloud patterns over the Indian Ocean during June 1967 - MISHRA, D. K.; SINGH, M. S. (MAUSAM, 1980)
The satellite cloud imagery over Indian Ocean for the month of June 1967 showed extensive cloud bands, thousands of kilometres in length, originating in south Indian Ocean. These cloud bands were aligned along the southeasterly trades, and curved sharply near the axis of southern hemispheric equatorial trough between Lat. 3 deg. S and 10 deg. S. The small scale cloud features, aligned to the low level wind field, showed prominently this turning across the axis of the trough and the equator-crossing of the deflected southwesterly current. There were indications of trade wind inversion in the southeasterlies in the form of cellular cloud patterns. The deuected southwesterly current and convective cloud clusters whose activity was maximum in the sea area north of the equator.